Bioproduction of propionic acid using levulinic acid by engineered Pseudomonas putida - Tiwari, Rameshwar; Sathesh-Prabu, Chandran; Lee, Sung Kuk (Frontiers in Bioengineering and Biotechnology, 2022)
The present study elaborates on the propionic acid production by the well-known microbial cell factory Pseudomonas putida EM42 and its capacity to utilize biomass-derived levulinic acid (LA). Primarily, the P. putida EM42 strain was engineered to produce propionic acid by deleting the methylcitrate synthase (PrpC) and propionyl-CoA synthase (PrpE) genes. Subsequently, a LA-inducible expression system was employed to express yciA (encoding thioesterase) from H. influenzae and ygfH (encoding propionyl-CoA: succinate CoA transferase) from E. coli to improve the propionic acid (PA) production by up to 10-fold under flask scale cultivation. The engineered P. putida EM42:ΔCE:yciA:ygfH was used to optimize the bioprocess to further improve the PA production titer. Moreover, the fed-batch fermentation performed under optimized conditions in a 5 L fermenter resulted in the titer, productivity, and molar yield for PA production of 26.8 g/L, 0.3 g/L/h, and 83 %, respectively. This study, thus, successfully explored the LA catabolic pathway of P. putida as an alternative route for the sustainable and industrial production of propionic acid from LA.